Gene Expression Profiling in Familial Adenomatous Polyposis Adenomas and Desmoid Disease - Bowden, Nikola A (BioMed Central, 2007)
Gene expression profiling is a powerful method by which alterations in gene expression can be interrogated in a single experiment. The disease familial adenomatous polyposis (FAP) is associated with germline mutations in the APC gene, which result in aberrant β-catenin control. The molecular mechanisms underlying colorectal cancer development in FAP are being characterised but limited information is available about other symptoms that occur in this disorder. Although extremely rare in the general population, desmoid tumours in approximately 10% of FAP patients. The aim of this study was to determine the similarities and differences in gene expression profiles in adenomas and compare them to those observed in desmoid tumours. Illumina whole genome gene expression BeadChips were used to measure gene expression in FAP adenomas and desmoid tumours. Similarities between gene expression profiles and mechanisms important in regulating formation of FAP adenomas and desmoid tumours were identified. This study furthers our understanding of the mechanisms underlying FAP and desmoid tumour formation.